COMMUNICATORY PARADIGM IN CONFLICTOLOGY - A. V. Scherbina (Дискурс, 2017)
This paper covers the heuristic potential of social conflict analysis in the communicatory paradigm, which allows enriching of Russian conflictology with methods of modern linguistics. Methodological guidelines are outlined for discourse analysis of a social conflict as a process with latent and explicit phases. Special attention is paid to the concepts of communicative conflict and conflict discourse.